The Innovativeness and Value of Quick Response Code Payment for MSMEs: The Influence of Security-Related Factor - Ayatulloh Michael Musyaff; Razana Juhaida Johari; Christian Wiradendi Wolor; Amer Azlan Abdul Jamal; Anaya Zahra Santika; Muhammad Arifsyah Arif (Bulgarian Academy of Sciences, 2023)
The implementation of QR code technology aims to make it easier for MSMEs and consumers to create a cashless society. However, many MSMEs still need to implement digital payment methods over time. This research aims to evaluate the acceptance of QR codes for MSMEs, especially regarding the role of innovativeness, security, and ease of use. This research targets MSMEs in Indonesia that have used the QR Code as a tool for making transactions. Questionnaires were distributed via Google form online, totalling 489 respondents who filled out. After the data is obtained, it is analyzed using a partial least square using smart-pls 4.0. Behaviour intention (BIQ) is the most influential construct on user behaviour (UBQ). The other most significant factors are convenience (PEUQ) and security (PSQ) for users. Meanwhile, other variables such as Personal innovativeness (PI), PEUQ, PSQ, and perceived usefulness (PUQ) can increase the positive impact on Perceived value (PVQ). Several factors, such as PEUQ and PSQ, can positively influence PUQ. However, there is a construct with few results: Perceived usefulness on intention to use. This is because MSMEs are more oriented toward consumer needs to buy products and services. So these findings provide insight for the government and service providers to improve security, convenience, and necessary QR code features that support MSME business activities